Theories and Major Hypotheses in Ethnobotany - Gaoue, Orou G.; Coe, Michael A.; Bond, Matthew; Hart, Georgia; Seyler, Barnabas C.; McMillen, Heather (Economic botany, 2017)
Ethnobotany has evolved from a discipline that largely documented the diversity of plant use by local people to one focused on understanding how and why people select plants for a wide range of uses. This progress has been in response to a repeated call for theory-inspired and hypothesisdriven research to improve the rigor of the discipline. Despite improvements, recent ethnobotanical research has overemphasized the use of quantitative ethnobotany indices and statistical methods borrowed from ecology, yet underemphasized the development and integration of a strong theoretical foundation. To advance the field of ethnobotany as a hypothesis-driven, theoretically inspired discipline, it is important to first synthesize the existing theoretical lines of research. We review and discuss 17 major theories and hypotheses in ethnobotany that can be used as a starting point for developing research questions that advance our understanding of people-plant interactions. For each theory or major hypothesis, we identify its primary predictions and testable hypotheses and then discuss how these predictions have been tested. Developing research to test these predictions will make significant contributions to the field of ethnobotany and create the critical mass of primary literature necessary to develop meta-analyses and to advance new theories in ethnobotany.